The importance of red cell distribution width and neutrophil-lymphocyte ratio as a new biomarker in rheumatoid arthritis - Koca, Tuba Tülay; Arslan, Aydın; Çiledağ Özdemir, Filiz; Berk, Ejder (The European Research Journal, 2019)
Objectives: Rheumatoid arthritis (RA) is a long-lasting autoimmune disorder that primarily affects the joints. Various biomarkers have been used for the prognosis and clinical follow-up. There are few studies that have investigated whether or not neutrophil-lymphocyte ratio (NLR) and red cell distribution width (RDW) are good indicators of systemic inflammation. The present study aims to explore the prognostic value of RDW and NLR in rheumatoid arthritis (RA) as a new inflammatory marker. Methods: RA patients (n = 124) who presented to the Rheumatology outpatient clinic in our hospital between March 2015 and May 2015 were included in this study retrospectively. As a first group, 47 clinically active RA patients who had high acute phase proteins were included. In the second group, 73 clinically in-remission RA patients who had normal acute phase proteins were included. Fifty-five healthy volunteers constituted the control group. Results: The mean RDW was found to be 15.2 ± 2.9 in the active group; 14.6 ± 2 in the inactive group and 13.4 ± 1.4 in the control group (p < 0.01). The mean NLR was found to be 3.7 ± 2.2 in the active group; 3.7 ± 1.6 in the inactive group and 3.2 ± 0.9 in the control group (p = 0.190). There were statistically significant differences between the RDW values of the active-period RA patients with the control group (p < 0.01). There was statistically significant difference between RDW values of active RA and inactive RA patients (p < 0.01). The NLR results between the RA group and the control group (p = 0.700); the active RA group, and the inactive RA group (p = 0.169) were similar. There was not statistically difference between the NLR values of active RA patients with the control group (p = 0.360). There was statistically difference between the NLR values of inactive RA patients with the control group (p = 0.047). Conclusion: RDW was found higher in all RA group than control, additionally was also higher in active RA group than remission group. NLR values of remission group was higher than control.